Inappropriate drug use among older persons: is it time for action? - Schoenenberger, Andreas W.; Stuck, Andreas E. (Age & Ageing, 2014)
The authors reflect on the improper use of drugs in elderly persons. The authors state the risk and potential benefit of drugs accompanied with pathophysiological changes during the ageing process and encounter of adverse drug reactions (ADRs). The authors also mention the research on the assessment of prevalence among older in-hospital patients.